2013
DOI: 10.11613/bm.2013.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sample hemolysis in blood collected by S-MonovetteR using vacuum or aspiration mode

Abstract: Background:In vitro hemolysis can be induced by several biological and technical sources, and may be worsened by forced aspiration of blood in vacuum tubes. This study was aimed to compare the probability of hemolysis by drawing blood with a commercial evacuated blood collection tube, and S-Monovette used either in the “vacuum” or “aspiration” mode.Materials and methods:The study population consisted in 20 healthy volunteers. A sample was drawn into 4.0 mL BD Vacutainer serum tube from a vein of one upper arm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…We hypothesized that the LD data were sensitive to damage during transport, and the diagnostics are inexpensive and easy to perform. In addition, LD levels were used as hemolysis indexes when drawing blood [11]. The measurements were performed before the flights, after the flights, and after the blood passed through a transfusion filter which removes fibrin and other components not necessary for transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the LD data were sensitive to damage during transport, and the diagnostics are inexpensive and easy to perform. In addition, LD levels were used as hemolysis indexes when drawing blood [11]. The measurements were performed before the flights, after the flights, and after the blood passed through a transfusion filter which removes fibrin and other components not necessary for transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies comparing vacuum collection systems against aspiration systems on larger scales are rare and conflicting. Lippi et al compared the Becton Dickinson (BD) Vacutainer™ system against the Sarstedt system, in both vacuum and aspiration mode, in 20 healthy volunteers and showed that blood collection by vacuum, regardless of the vendor, increases hemolysis rates [9]. In two subsequent retrospective studies, Lippi et al as well as Goegebuer et al confirmed a reduction in hemolysis rates by the use of an aspiration system compared to a vacuum system [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…One of these variables is the type of blood collection system in use [5][6][7][8]. Vacuum systems are known to increase the rate of hemolytic specimen compared to aspiration systems due to higher shear stress, subsequently leading to damage of red blood cells [7,9]. This might be avoided by the use of low vacuum tubes, although the literature to this topic is conflicting [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Microtiter plate biofilm assays were carried out as described previously (14). Briefly, blood (approximately 40 ml) was drawn from a healthy volunteer using the S-Monovette system (Sarstedt) containing heparin or EDTA (15). Blood was transferred into 15-ml tubes and centrifuged at 150 ϫ g for 10 min.…”
Section: Methodsmentioning
confidence: 99%